Peran Guru Bimbingan dan Konseling Dalam Meningkatkan Minat Belajar Siswa di SMP IRA - Wirda Selvya Tambunan; Ahmad Syarqawi (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The purpose of this study was to find out how the guidance and counseling teachers at SMP IRA contributed to increasing student interest in learning. Qualitative descriptive method used in this study. Guidance and counseling teachers, subject teachers, homeroom teachers, and representatives of class VII B and VIII B IRA Middle School students were used as research data sources. In addition to the ineffectiveness of cooperation between guidance and counseling teachers, subject teachers, and homeroom teachers, parents who do not understand the importance of education for their children are an inhibiting factor for services. Therefore, having an interest in student learning is also very important to channel interest in a subject or learning without any coercion from anyone. Keywords: The role of the teacher, student interest, and learning